Analysis of patient load data for teams competing in the 2003 Cricket World Cup in South Africa - Killian, A; Stretch, RA (South African Journal of Sports Medicine, 2006)
Objectives. To evaluate the injury presentation data for all teams taking part in 10 warm-up matches and 46 matches during the 2003 Cricket World Cup played in South Africa, in order to provide organisers with the basis of a sound medical-care plan for future tournaments of a similar nature. Methods. The data collected included the role of the injured person, the nature of the injury, whether the treatment was for an injury or an illness, whether the injury was acute, chronic or acute-on-chronic, and the prognosis (rest, play, unfit to play, sent home, follow-up treatment required). The medical personnel in charge of the medical support documented patient information which included the total number of patient presentations and the category of illness/injury. Results. Ninety patient presentations (1.6 patient presentations per match) were recorded. The most common patient presentations were by the batsmen (50%), followed by the bowlers (29%) and all-rounders (17%). Of the patient presentations, 53% were classified as injuries, while the remaining 47% were classified as illnesses. The patient presentations occurred in the early stages of the competition. The most common presentations were of an acute nature (63%). The main injury pathology categories were trigger point injuries (10%), and bruises / abrasions (10%), while infection (29%) was the main illness pathology. Conclusions. The 2003 Cricket World Cup proved to be an ideal opportunity to collect data on international cricketers participating in an intensive 6-week international competition; the epidemiological data collected should assist national cricket bodies and organisers of future Cricket World Cup competitions to predict participant-related injury rates. South African Journal of Sports Medicine Vol. 18 (4) 2006: pp. 129-134